Transnasal Prelacrimal Recess Approach for Recurrent Antrachoanal Polyp. Issue 4 (June 2016) - Comoglu, Senol; Celik, Mehmet; Enver, Necati; Sen, Comert; Polat, Beldan; Deger, Kemal
Abstract : Purpose: To assess the effectiveness and usefulness of transnasal prelacrimal recess approach (TPRA) in patients with recurrent antrochoanal polyps. Methods: Twelve patients with antrochoanal polyp recurrence underwent surgery with a transnasal endoscopic prelacrimal recess approach. Success for visualization of the origin of the polyps, surgical complications, and recurrence was evaluated. Results: Transnasal prelacrimal recess approach was successful in 83% of the patients (10/12); polyps that originated from a posterior location (2 patients) were excised using the middle meatal approach. Nasolacrimal duct injury occurred in 2 patients but neither had epiphora postoperatively. Three patients (3/12; 25%) had synechia formation between the lateral nasal wall and septum just superior to the inferior turbinate. One of the 3 patients (1/12; 8.3%) with synechia was symptomatic and required surgical treatment under local anesthesia. During a mean follow-up period of 14.2 months (range, 8–21 months) no recurrence had developed. Conclusion: In experienced hands, TPRA is a novel, reliable, and useful method for the treatment of recurrent antrochoanal polyps. It ensures good exploration of the maxillary antrum and easy access to the polyp origin on the maxillary wall without the need of additional approaches.